Multi-Unit Assignment Problem: FCFS Course Allocation System Data Analysis - Murauskas, Gediminas; Radavičius, Marijus (Lithuanian Journal of Statistics, 2016)
We study the allocation of courses to students with multi-unit demand. Exploratory analysis of courseallocation practices at Vilnius University (VU) is performed. The allocation of students to courses is done by a simplefirst-come first-served (FCFS) procedure. We show that FCFS procedure does not deliver desirable outcomes. Data withstudent preferences is needed in order to compare assignment algorithms. We use censored regression model to constructstudent preferences generation mechanism based on empirical data collected at VU. Using simulated data several multiunitassignment algorithms are compared.
Keywords: multi-unit assignment; FCFS; preferences; censored regression